Hubungan Tingkat Pengetahuan Mengenai Zat Besi Dengan Tingkat Kepatuhan Mengkonsumsi Tablet Besi Pada Ibu Hamil Di Puskesmas Sibela Mojosongo Surakarta - Dwi Tiara Septiani; Erick Edwin; Bambang Sukilarso (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Anemia in pregnant women increases the frequency of complications of pregnancy and childbirth. Anemia due to iron deficiency is a major cause of anemia in pregnant women compared with deficiencies of other nutrients. Iron anemia prevention programs, especially for pregnant women has been done through the provision of iron for free through the health center or posyandu. However, because of the limited knowledge of most of the pregnant women then this program seem to run slow. This study aims to demonstrate a link between the level of knowledge about the level of compliance with the iron taking iron tablets. Methods: This study was an observational analytic cross-sectional approach. Subjects were pregnant women Sibela Mojosongo the Surakarta Health Center. Sample of pregnant women who took iron tablets. Samples were taken by purposive sampling. The data collection technique using a questionnaire concerning the knowledge level of iron, the level of knowledge questionnaires and scales consuming iron tablets LMMPI inventory. Data score of knowledge about iron with Compliance Consuming Iron Tablets in pregnant women were analyzed with chi square test. Results: Obtained 30 samples of pregnant women. The results of chi-square analysis showed that there is a positive relationship between the level of knowledge regarding iron with adherence consuming iron tablets at the health center Mojosongo Sibela Surakarta. that patients with a high level of knowledge has compliance 35 times higher than those knowledgeable with p = <0.001 (OR = 35; 95% Cl 2.977 411.466 sd). Conclusions: Based on this study it can be concluded that there is a correlation between the level of knowledge about the level of compliance with the iron taking iron tablets to pregnant women. The higher the mother's level of knowledge of the iron, the higher the level of compliance in consuming iron tablets Keywords: Pregnant women, knowledge of iron, compliance consuming iron tablets